RSPO CERTIFICATION AS A MODERATOR IN THE ESG–FIRM VALUE NEXUS: EVIDENCE FROM SOUTHEAST ASIAN PALM OIL INDUSTRY - Khalilul Rahman; Sanda Patrisia Komalasari; Muhammad Wafiq; Yana Mustika (IJMA (Indonesian Journal of Management and Accounting), 2025)
This study is necessary to measure the effects of variables that can provide insights into firm value, particularly for palm oil companies in Southeast Asia. The impact of Environmental, Social, and Governance (ESG) performance on firm value in Southeast Asia’s palm oil industry, emphasizing the moderating role of Roundtable on Sustainable Palm Oil (RSPO) certification. Data from 26 publicly listed companies in Indonesia, Malaysia, and Singapore are analyzed using OLS regression with STATA 17. ESG data are sourced from SPOTT (2019â€“2023), and financial data from Thomson Reuters up to December 2023. Results reveal a significant negative effect of ESG performance on firm value, likely due to short-term cost perceptions. However, RSPO certification positively moderates this relationship by improving market perception and mitigating negative effects. This study contributes new insights into the ESGâ€“firm value nexus, highlighting the strategic importance of sustainability certification. Firms are encouraged to adopt integrated sustainability strategies, while regulators should promote sustainable practices through incentive-based policies.